PENERAPAN LEAN MANUFACTURING UNTUK MENINGKATKAN KAPASITAS PRODUKSI DENGAN CARA MENGURANGI MANUFACTURING LEAD TIME STUDI KASUS: PT ORIENTAL MANUFACTURING INDONESIA - Sumiharni Batubara; Raden Abdurrahman Halimuddin (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2016)
PT Oriental Manufacturing Indonesia is a company engaged in the manufacturing industries that produce plastics components for the automotive industry. The main problem that occurs is the target production of Final Assy. Front Door is not reached as a manufacturing lead time (MLT) is too long.The purpose of this research is to reduce the Manufacturing Lead Time (MLT) so that production targets can be achieved. Lean Manufacturing approach used to reduce the waste that occurs. The first step is to create Value Stream Mapping (VSM), which describes the overall process. From the VSM waste can be identified in the some activities (changeover mold) and one activity (final inspection). MLT improvement performed by using Single Minute Exchange of Dies on mold changeover activity and Left Hand Right Hand Mapping on the final inspection process. As the result of improvement, the value of process cycle efficiency has increased by 11.35% from 36,88% to 48,55%. Manufacturing Lead Time has decreased from 35.327 seconds to 26.834 seconds.